Case report: Drug-drug interaction between alectinib and apixaban in NSCLC - J.L. Gulikers; M. Slikkerveer; K. Winckers; L.E.L. Hendriks; S. Dursun; S. Croes; R.M.J.M. van Geel (Current Problems in Cancer: Case Reports, 2022)
Plasma concentrations of direct oral anticoagulants (DOAC) are potentially affected because of drug-drug interactions (DDI) with anticancer treatment as a result of inhibition or induction of CYP3A4, p-glycoprotein (P-gp) and/or Breast Cancer Resistance Protein (BCRP) interactions.Here, we present a 78-year-old patient with non-small cell lung cancer (NSCLC) receiving treatment with alectinib concurrent with apixaban as prophylactic treatment of recurrent thrombophlebitis. Given the unexpected high apixaban plasma concentrations, the apixaban dose was reduced stepwise to 25% of its original dose in order to achieve values within the on-therapy reference range. This case demonstrates that monitoring DOAC plasma concentrations may be indicated when DOACs are used concurrently with alectinib.